Earliest Arrival of Evacuees with Contraflow Approach - Gupta, Shiva Prakash; Khadka, Shree Ram (Journal of the Institute of Engineering, 2017)
The earliest arrival flow problem sends a maximum number of evacuees as early as possible during the evacuation of people and/or property from dangerous zone to the safe zone. The contraflow approach significantly increases the capacity to send the evacuees at one hand and reduces the time the evacuation takes on the other hand. The problem has been extensively studied as an optimization problem with wide application. In this paper we briefly revisit the existing literature of the problem. Journal of the Institute of Engineering, 2016, 12(1): 96-104